Respuesta :

AL2006

It's an expression that's made out of the product of two binomials.

When the indicated multiplication is carried out, the expression reads:

a²b² - ab - 72

ANSWER

[tex](ab-9)(ab+8) = {(ab)}^{2} - ab - 72[/tex]

EXPLANATION

We want to expand (ab-9)(ab+8)

We use the distributive property to obtain,

[tex](ab-9)(ab+8) = ab(ab+8)-9(ab+8)[/tex]

Expand:

[tex](ab-9)(ab+8) = {(ab)}^{2} +8ab-9ab - 72[/tex]

Combine the middle terms to get;

[tex](ab-9)(ab+8) = {(ab)}^{2} - ab - 72[/tex]

Or

[tex](ab-9)(ab+8) = a^2b^2 - ab - 72[/tex]